My Revision Notes : CCEA GCSE English Language - Barr, Amanda; Northern Ireland Council for the Curriculum, Examinations and Assessment (London : Hodder Education, 2018)
Target success in CCEA GCSE English Language with this proven formula for effective, structured revision; clear guidance is combined with exam-style tasks and practical tips to create a revision guide that students can rely on to review, strengthen and test their skills. With My Revision Notes every student can: - Plan and manage a successful revision programme using the topic-by-topic planner - Feel confident tackling each question type by completing tasks for Reading and Writing in Units 1 and 4 - Practise exam skills with 'Test Yourself' activities, supported by easy-to-understand mark.
Task 2: Comparing literary textsReading literary texts; Comparing texts; What to look for when comparing and contrasting; Language to compare and contrast; Tasks 3 and 4: Reading non-fiction texts; Understanding writers' attitudes and intentions; Analysing techniques; Evaluating the effect; Test yourself answers.
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Description based on online resource; title from digital title page (viewed on April 11, 2019).
Added to collection customer.56279.3
Keywords: English language -- Composition and exercises -- Examinations -- Study guides; English language -- Written English -- Examinations -- Study guides; English language -- Examinations -- Study guides; English language -- Study and teaching (Secondary) -- Northern Ireland; EDUCATION / Higher; Electronic books